Approaches to the field recognition of potential thrombectomy candidates. Issue 7 (October 2017) - van Gaal, Stephen C; Kamal, Noreen; Betzner, Michael J; Vilneff, Renee L; Mann, Balraj; Lang, Eddy S; Demchuk, Andrew; Buck, Brian; Jeerakathil, Thomas; Hill, Michael D
Systems of care for acute ischemic stroke are being challenged to implement processes that ensure rapid access to endovascular thrombectomy. Optimizing existing regionalized stroke thrombolysis programs for endovascular thrombectomy will require accurate field recognition of treatment candidates. We begin with a review of the development of early clinical tests for ischemic stroke, illustrating challenges relevant to future field tests for large vessel occlusion. Second, we discuss aspects of diagnosis, eligibility, feasibility, and system organization that are potentially relevant to the development and implementation of field tests and diversion criteria. These considerations may influence the choice and parametrization of field tests in individual jurisdictions. Third, we review the literature evaluating eight clinical tests for the field identification of probable large vessel occlusion. All candidate tests include evaluations for focal weakness, and six evaluate for cortical signs such as aphasia or gaze deviation. Most appear roughly comparable to the NIH Stroke Scale, but direct comparison between studies is inappropriate because of major methodological differences. Finally, we discuss our jurisdiction's approach to the field recognition of thrombectomy candidates. We contextualize diagnostic, eligibility, and system considerations within distinct metro and rural environments and propose a screen-and-consult model for the rural setting.